The Issue of Labour in Germany in the Galicia District Press: Content Analysis - Mosora , Volodymyr (Studia Historiae Oeconomicae, 2024)
The article presents the content analysis of publications on the labour in Germany that were published on the territory of the Halychyna (Galicia) region during the German occupation of 1941–1944. All the articles, namely 104 of them published in 14 periodicals (Volia Pokuttia, Ukrainske Slovo, Vilne Slovo, Holos Pidkarpattia, Drohobytske Slovo, Zborivski Visti, Zolochivske Slovo, Lvivski Visti, Ridna Zemlia, Sokalske Slovo, Stanislavivske Slovo, Krakivski Visti, Ternopilskyi Holos and Chortkivska Dumka), were divided into several groups: "Type of publication", "Time" and "Placement". Each group underwent the word cloud type of analysis, and it provided an opportunity to thoroughly study peculiarities of the printed materials of the Nazi occupation period. Additionally, the article presents the cross-analysis of these groups in an attempt to trace their possible interconnection. The main objective of this paper is to use the content analysis method to analyse German propaganda policy of the time encouraging Galician workers to work in Germany and the way the policy changed over the time. The application of new research methods, in particular the content analysis method, to the study of the topic of Galician work force relocation to Germany on the materials from the Galician periodicals, contributes to the novelty of the paper. Summing up, one should say that the German authorities’ labour policy aimed at the Galician population was not consistent and constantly changed.